1975
DOI: 10.1021/j100590a015
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide adsorption on supported ruthenium

Abstract: The infrared spectra of CO adsorbed on alumina-supported ruthenium catalysts reveal one band when the metal particles are large and three bands when the particles are small. One band is assigned to CO adsorbed on low index planes of the Ru, while two of the bands are associated with CO adsorbed on low coordination edge and corner metal atoms. Comparison of CO adsorption to H2 adsorption reveals CO/H ratios as high as 4 on Ru particles of 11 Á diameter implying multiple adsorption of CO on low coordination site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(39 citation statements)
references
References 2 publications
6
33
0
Order By: Relevance
“…Their data could be fit quite nicely using first order desorption kinetics 151 which are indicative of non-dissociated carbon monoxide. These results are in agreement with those of Madey and Menzel on ruthenium (0001).Several infrared studies involving carbon monoxide on supported ruthenium catalysts have been reported recently[112][113][114][115][116]. Each reports that the carbon monoxide molecule is non-dissociated on ruthenium.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Their data could be fit quite nicely using first order desorption kinetics 151 which are indicative of non-dissociated carbon monoxide. These results are in agreement with those of Madey and Menzel on ruthenium (0001).Several infrared studies involving carbon monoxide on supported ruthenium catalysts have been reported recently[112][113][114][115][116]. Each reports that the carbon monoxide molecule is non-dissociated on ruthenium.…”
supporting
confidence: 89%
“…f few of these would, however, not change the order dependence of the rate | law in the desired manner. If we examine equation (112) it is apparent that in order to increase the negative order dependence in terms of i hydrogen we must either change the rate limiting step such that the exponent of the hydrogen term in the numerator is less than +2 or we must add a term in the denominator which goes as the hydrogen pressure raised to a power greater than +3/2. The numerator has a very significant effect upon the fit of the theory to the data, especially in the positive order region of the hydrogen order plot.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…In this case, strong binding of PCy 3 on the catalyst surface blocks the catalytically active sites. Additionally, carbon monoxide and thiophene were used separately as catalyst poisons, wherein suppression of catalytic activity was noted for carbon monoxide and thiophene treated catalyst (Ru‐TBAB). Since, ruthenium nanosponge exhibits good catalytic activity towards arene hydrogenation, it would be important to study the effect of alloying with other metals to understand the catalytic activity at moderate reaction conditions with lower catalyst loading.…”
Section: Resultsmentioning
confidence: 99%
“…Comparable correlations between Ru particle size and the relative population of on-top and bridge-bonded adsorbed CO were also reported in an umber of previous studies. [41][42][43] This was explained by the formation of linearly bound CO ad species for adsorption on low-coordination edge and corner atoms, the relative contribution of whichi ncreasesw ith decreasing particles ize. [44,45] Another notable consequence of activation in wet reformatei st he lower coverage of surface formates rela- tive to that obtaineda fter activation in dry SR-ref 6000.…”
Section: Time Evolution Of the Adlayermentioning
confidence: 99%